Pattern of Tumour among Hepatocelluar Carcinoma Patients attended at a Tertiary Care Hospital in Dhaka City - Hossain, Md Akter; Haque, Md Saiful; Rahman, Md Ashikur; Nasreen, Zinat; Bhuiya, Mostaque Ahmed; Siddique, Abu Bakar (Journal of Current and Advance Medical Research, 2019)
Background: The pattern of hepatocelluar carcinoma may vary in different patients. Objective: The purpose of the present study was to see the pattern of hepatocelluar carcinoma among the patients attended at a tertiary care hospital in Dhaka city. Methodology: This cross-sectional study was carried out in the Department of Radiology and Imaging at Dhaka Medical College, Dhaka and Banghabandhu Sheikh Mujib Medical University, Dhaka from January 2007 to May 2008 for a period of around one and half year. All the patients presented with hepatocellular carcinoma at the age group of more than 20 years with both sexes were selected as study population. The patients were undergone CT-scan examination and the confirmation was performed by histopathological examination. The details of the pattern of tumor among the hepatocellular carcinoma patients were examined and were recorded. Result: A total number of 50 patients were recruited in this study after fulfilling the inclusion and exclusion criteria. Mean age with SD of study population was 48.78 ±12.07. Within 25 cases of HCC as diagnosed by CT scan 13(52%) had solitary lesion 7(28%) had multiple lesions and remaining 5(20%) had diffuse lesions. The tumour size of 8 cm or more was the highest which was 10 in numbers. However, 4 to 8 cm was found in 7(28.0%) cases and 3 to 4 cm was detected in 3(12.0%) cases. Conclusion: In conclusion most of the HCC is solitary lesion with more than 8 cm in size. Journal of Current and Advance Medical Research 2019;6(1):6-9